Brief Report: Anti–Tumor Necrosis Factor α Targets Protein Kinase B/c‐Akt–Induced Resistance of Effector Cells to Suppression in Juvenile Idiopathic Arthritis. Issue 12 (27th November 2013) - Wehrens, Ellen J.; Vastert, Sebastiaan J.; Mijnheer, Gerdien; Meerding, Jenny; Klein, Mark; Wulffraat, Nico M.; Prakken, Berent J.; van Wijk, Femke
Abstract : Objective: To determine whether therapeutic strategies that block interleukin‐6 (IL‐6) or tumor necrosis factor α (TNFα) can improve the responsiveness of Teff cells to suppression in patients with juvenile idiopathic arthritis (JIA). Methods: Synovial fluid mononuclear cells (SFMCs) from the inflamed joints of patients with JIA were cultured in the presence of etanercept or anti–IL‐6 in vitro, and protein kinase B (PKB)/c‐Akt activation and responsiveness to suppression were measured. In addition, the in vivo effects of TNFα blockade were investigated using peripheral blood mononuclear cells obtained from patients before and after the start of etanercept therapy. Results: In vitro treatment of SFMCs with anti–IL‐6 led to improved Treg cell–mediated suppression of cell proliferation in some but not all patients. Blocking TNFα with etanercept, however, clearly enhanced suppression, especially that of CD8+ T cells. In the presence of etanercept, PKB/c‐Akt activation of Teff cells was reduced, and cells became more susceptible to transforming growth factor β–mediated suppression, indicating that anti‐TNFα directly targets resistant Teff cells. Conclusion: This study is the first to show that anti‐TNFα targets the resistance of Teff cells to suppression, resulting in improved regulation of inflammatory effector cells.